Knowledge and Practice of Employed Mothers towards Exclusive Breastfeeding and Its Associated Factors in Mecha District, Northwest Ethiopia - Amare Lisanu Mazengia; Hibru Demissie (Journal of Nutrition and Metabolism)
Background. Exclusive breastfeeding is an important strategy for improving child health. However, the practice of exclusive breastfeeding among employees is very low in developing countries including Ethiopia. Objective. The objective of this study was to assess the knowledge and practice of employed mothers towards exclusive breastfeeding and its associated factors in Mecha district, Amhara Region, Northwest Ethiopia, 2019. Methods. A cross-sectional study was conducted from April 05 to June 30, 2019. A stratified random sampling technique was applied. Data were analyzed using statistical package for social sciences (SPSS) version 23 software. Multivariate logistic regression was used to determine predictors of knowledge and practice. Result. A total of 449 participants were enrolled with a response rate of 95.54%. The study revealed that 92.1% (95% CI: (89.5–94.6)) of participants had good knowledge. However, only 38.5% (95% CI: (33.8–42.9)) employed mothers breastfeed their babies exclusively. Certain predictors such as maternity leave (AOR = 0.31, 95% CI:(0.10–0.91), p value = 0.03), mothers’ level of education (AOR = 2.97, 95% CI: (1.66–5.34), p value <0.001), support from husbands(AOR = 0.26, 95% CI (0.14–0.47), p value <0.001), and actual time to return back to their work(AOR = 0.21; 95% CI: (0.08–0.51), p value = 0.01) were statistically associated with exclusive breastfeeding. Conclusions and Recommendations. The knowledge and practice of employed mothers towards exclusive breastfeeding were affected by the number of predictors. Exclusive breastfeeding practice among employed mothers was low. It is advisable to give some flexible working hours for breastfeeding mothers.